2022
DOI: 10.1002/rem.21727
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ soil washing to remove PFAS adsorbed to soils from source zones

Abstract: This article presents the results of an Environmental Security Technology Certification Program (ESTCP) demonstration conducted at Eielson Air Force Base in Fairbanks, Alaska: Ex situ soil washing to remove per-and polyfluoroalkyl substances (PFAS) adsorbed to soils from source zones. The ESTCP project information can be found here: https://www.serdp-estcp.org/Program-Areas/ Environmental-Restoration/Risk-Assessment/ER20-5258. The final report is expected to be published in September 2022. The objective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These studies have shown that PFAS is associated typically with fines and organic/humic materials within the soil. Pilot work is being conducted to demonstrate PFAS removal and assess removal efficiency for each size fraction and to demonstrate treatment costs (Grimison et al, 2023; Quinnan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that PFAS is associated typically with fines and organic/humic materials within the soil. Pilot work is being conducted to demonstrate PFAS removal and assess removal efficiency for each size fraction and to demonstrate treatment costs (Grimison et al, 2023; Quinnan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Today, a wide selection of options exists for remediation of soil contamination, such as biological degradation, (catalyzed) chemical oxidation, stabilization, soil washing and thermal treatment processes (Quinnan et al, 2022;Ross et al, 2018;Travar et al, 2020). However, many of these treatments only have limited effect, due to the recalcitrance and behaviour of PFAS in the environment.…”
Section: Introductionmentioning
confidence: 99%